Hans Enoch and vivicillin. (May 2018) - Shama, Gilbert
Hans Emmanuel Enoch (1896–1991) was born in Hamburg, the son of a manufacturer of sera and vaccines. Upon his father's death, he took charge of the Hamburg Serum Werke . Following the rise of Hitler, he came to be pilloried in the Nazi press for allegedly having poisoned the population of Hamburg and was imprisoned for a time. He immigrated to England in 1935 where he had secured a position with the International Serum Company in Norwich. Following the outbreak of war, he was interned as an enemy alien, eventually ending up in Canada. In 1941, he was permitted to return to England, but wartime conditions prevented him from continuing to manufacture sera. At about this time, penicillin was making the headlines, and coupled with accounts of its miraculous properties, was the news that all production was reserved exclusively for the armed forces. Enoch decided to meet the public clamour for penicillin by producing a crude version which he termed 'vivicillin.' News of this spread globally, and he came to incur the disdain of Howard Florey for the attendant publicity. Notwithstanding this, vivicillin was to prove itself effective and its use led to the saving of lives.